Streets of fire Bruce Springsteen in photographs and lyrics, 1977 - 1979 - Springsteen, Bruce 1949- (ItBooks, 2012)
Photographs of the musician from 1977-1979, interspersed with full lyrics, lyric selections, and essays by the photographer
Badlands -- Adam raised a Cain -- Something in the night -- Candy's room -- Racing in the street -- The promised land -- Factory -- Streets of fire -- Prove it all night -- Darkness on the edge of town
Keywords: Springsteen, Bruce; Springsteen, Bruce / Portraits; Springsteen, Bruce -- 1949-; Geschichte 1977-1979; Rock musicians / United States / Portraits; Rock music / Texts; Songs / Texts; Porträtfotografie; Song; Text; USA; Bildband